2012
DOI: 10.1016/j.jaci.2012.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications and improved regulatory T-cell function in subjects undergoing dual sublingual immunotherapy

Abstract: Background Allergen-specific immunotherapy is the only mode of therapy that has been demonstrated to offer a cure in patients with IgE-mediated respiratory allergies. Objective We sought to demonstrate the safety and efficacy of timothy grass (TG) and dust mite (DM) dual sublingual immunotherapy (SLIT) and to begin to investigate the immune mechanisms involved in successful immunotherapy with multiple allergens. Methods The safety and efficacy of dual SLIT with TG and DM in children and adults with demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 39 publications
4
95
0
3
Order By: Relevance
“…35 On the other hand, Swamy et al observed a decrease of basophil activation after stimulation with specific allergens in a group of patients receiving dual SLIT (house dust mite and timothy grass) for 2 years. 36 Lack of changes in basophil sensitivity to specific allergens after 1 year of SLIT is thought to be associated with high affinity IgE receptor (FceRI) expression on the surface of basophils. It is postulated that B-cells primarily react to SLIT by increasing asIgE production.…”
Section: Discussionmentioning
confidence: 99%
“…35 On the other hand, Swamy et al observed a decrease of basophil activation after stimulation with specific allergens in a group of patients receiving dual SLIT (house dust mite and timothy grass) for 2 years. 36 Lack of changes in basophil sensitivity to specific allergens after 1 year of SLIT is thought to be associated with high affinity IgE receptor (FceRI) expression on the surface of basophils. It is postulated that B-cells primarily react to SLIT by increasing asIgE production.…”
Section: Discussionmentioning
confidence: 99%
“…142 A small study in children demonstrated efficacy using a mixture of grass pollen and HDM SLIT. 143 SLIT drops that employed a monomeric Phleum pratense grass pollen extract was more effective when given alone compared to when given in an equivalent dose as part of a combination with a 9-pollen, multi-allergen, sublingual extract. 100 There are a number of potential drawbacks of mixing allergens including a dilutional effect, potential allergen degradation due to enzymatic activity of some allergens and the difficulties of adequately demonstrating efficacy of a high number of allergen combinations and/or different products.…”
Section: Allergen Mixturesmentioning
confidence: 93%
“…4 T H 2 response downregulation, immunologic switch to T H 1 responses, or both suggest induction of tolerogenic pathways, 7-9 suppression of allergic inflammation, and generation of regulatory T (Treg) cells. 6,8,[10][11][12] Treg cells have multiple effects in controlling allergen-specific immune and IgE-mediated allergic inflammation. 13 These cells can induce dendritic cells that support further Treg cell generation and suppress effector T-cell differentiation 14 ; they also suppress T H 1 and T H 2 cells and induce IgG 4 , IgA, or both.…”
mentioning
confidence: 99%